SENSORS OF FLOWS OF BULK MATERIALS - KHODIACHIY, Vladislav; NIKITIN, Olexander (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In such branches of industry as agriculture, pharmaceutical, metallurgical, chemical, mining, and a number of others, it is necessary to determine the mass consumption and amount of loose material, grain, cereals, flour, specific components of chemical and pharmacological materials of cement, and the mass of others. Ways of measuring the consumption and amount of loose materials are a necessary component in the automation systems of modern production processes of the specified industries. Without the use of devices for measuring the consumption of loose materials, it is impossible to improve the production of products of the required quality and competitiveness. That is why issues related to the development, experimental research and use of these flowmeters are quite relevant.Production automation is one of the leading areas of scientific and technological progress. With the change or improvement of production technologies, the introduction of new types of equipment, the automation of production processes requires the development of specific methods and device of measurement. Most of the latest methods of measuring the consumption of bulk material allow you to automate the production process, which in turn makes it possible to reduce the cost of the product. The article considered the main types of sensors that can be used as part of ways of measuring the consumption of loose materials, such as cereals and grains. An analysis of the latest publications was made, both in domestic and in English-language publications. The considered sensors can be part of modern flow meters, the principles of which are based on various measurement methods.According to the fundamental of operation, flowmeters are divided into continuous and discrete, as well as mass and volumetric. The most common flowmeters are those that record flow using strain gauges. As accuracy and compact size allow you to use them in different conditions and with different loose materials. In the article, a lot of attention was paid to impact flowmeters. Based on the analysis of the fundamental of operation of flowmeters, the direction of development of flowmeters with the use of modern technologies to level the influence of flow characteristics on measurement errors will be promising. The results of the conducted review and analysis of flow sensors of loose materials are planned to be used in the future to create a computer-integrated system for identification of flow parameters of loose materials, which will make it possible to use automated control systems of technological processes more variably.
Keywords: grain flow; consumption of bulk materials; flow meter